Influence of Pre-Harvest Factors on the Storage of Fresh Basil (Ocimum basilicum L.): A Review - Michele Ciriello; Petronia Carillo; Matteo Lentini; Youssef Rouphael (Horticulturae)
Thanks to its numerous uses in gastronomy, pharmaceuticals, and cosmetics, basil (Ocimum spp.) is one of the most studied and consumed aromatic plants worldwide. However, its commercialization and availability are limited by its short post-harvest shelf-life, primarily due to its strong sensitivity to cold, poor handling, and consequent microbial contamination. This review provides a comprehensive overview of the latest research on pre-harvest techniques that can extend the shelf-life of basil, aiming to offer a practical tool for growers, distributors, retailers, and scientists. In addition to influencing the plant’s primary metabolism, pre-harvest factors, such as genotype selection, plant nutrition, irrigation, and light management, can have a direct impact on basil quality and shelf-life. Unlike previous reviews, which primarily focus on post-harvest strategies, this work provides a structured analysis of pre-harvest factors that directly influence basil’s shelf-life. By integrating recent findings on genotype selection, nutrient management, and environmental conditions, we offer a comprehensive framework to guide future agronomic practices aimed at minimizing post-harvest losses and enhancing product quality.